Percepción social de los docentes sobre las causas de la deserción escolar de los adolescentes en una institución educativa del Distrito, Turístico y Cultural de Riohacha - Pimienta Díaz, Daniela Liceth; Velázquez Bonivento, Alis Delia (Universidad Antonio Nariño, 2021)
School dropout is a problem that all countries in the world suffer and it raises concern because this problem not only affects the life of the student who drops out but society in general, education is the basis for a country to develop. The objective of this research was to describe the social perception of teachers about the causes of school dropout of adolescents in the Educational Institution Denzil Escolar headquarters Tawaira